IMPLEMENTASI PENDEKATAN TASK-BASED LANGUAGE TEACHING (TBLT) BERBASIS PROYEK DIGITAL DALAM MENINGKATKAN KETERAMPILAN BERBICARA (SPEAKING SKILLS) MAHASISWA NON-BAHASA INGGRIS: SEBUAH KAJIAN LITERATUR - Ananda Meisarah Harahap (Al-Insyirah: Jurnal Pendidikan dan Konseling Islam, 2026)
Oral communication skills in English are an essential competence for non-English department students to face global challenges. However, conventional teaching methods often fail to address foreign language anxiety and the lack of active student engagement. This study examines the implementation of the Task-Based Language Teaching (TBLT) approach combined with the utilization of digital projects as an alternative strategy in higher education English learning. Employing a literature review method, this article analyzes various relevant scientific literatures to evaluate the effectiveness of the model. The findings of the review indicate that TBLT is capable of providing an authentic communication space through the completion of meaningful tasks, while the integration of digital projects—such as podcasts, collaborative videos, and technology-based media—proves effective in motivating students, reducing anxiety levels, and improving speaking fluency and accuracy. Based on these results, educators are advised to adopt the integration of TBLT and digital media to create an interactive, student-centered learning ecosystem that is relevant to the demands of the modern workforce.